Directing Cell Front-Rear Polarization and Migration with Dynamic Micropatterning : Protein Coating and Cell Type Specific Differences - Saukkonen, Karla (My University, 2024)
Cell migration is fundamental in many physiological processes, including tissue repair and immune responses, as well as in pathological processes including chronic inflammation and cancer metastasis. Front-rear polarization and cell adhesion are essential steps of cell migration. Understanding the steps and mechanisms that regulate cell polarization and migration can enable designing therapeutic strategies that target these events. Micropatterning, i.e., controlling the distribution of surface molecules with microscale resolution, can be used to create patterns of adhesive surface areas and to control the placement and shape of living cells on the surface. Compared to traditional cell culture, single cell micropatterning reduces the variability between the cells and allows easy normalization of the cells, also between experiments. With dynamic micropatterning, areas between the attached cells, which are biologically inert, can be made permissive for cell-substrate adhesion, and thus attached cells can be released to migrate and create new cell-substrate and cell-cell connections in controlled and standardized manner. The development of dynamic micropatterns has enabled enjoying the benefits of micropatterning, while studying dynamic processes such as cell polarization and migration. In this thesis project we introduced a novel low-cost, easily accessible method for producing dynamic micropatterns by utilizing biotin-streptavidin binding. Experiments on coating efficacy, specificity and biocompatibility were performed to validate the method for use in academic cell research laboratories. It has been earlier demonstrated that asymmetric micropatterns, including crossbow-shaped micropatterns, can control and guide cell front-rear polarity. [Jiang et al., 2005; Théry et al., 2006] In this thesis we investigated whether the geometric control of cell polarity is influenced by the specific adhesive substrate the cells are adhering to. Indeed, immunofluorescence imaging of fixed cells on micropatterns revealed substrate-dependent differences in U-251 MG cell polarization. By live-imaging the dynamics of the cell front-rear polarization of U-251 MG cells on fibronectin and an anti-integrin antibody mAb13 -coated crossbow-shaped micropatterns, it was observed that although fibronectin was better at controlling the direction of the front-rear polarization, the direction of the front-rear polarization stayed rather static in both groups. Finally, the novel method of dynamic micropatterning was used to determine whether cell behavior at the onset of migration is affected by the adhesive ligand. Streptavidin-conjugated fibronectin allowed instant modification of the biotinylated surface, and U-251 MG cells rapidly migrated from both substrates to the newly modified areas. Again mAb13-coated micropatterns did not control the direction of the front-rear polarization as effectively as fibronectin-coated micropatterns, but in both groups most cells did spread and migrate towards the broader edge of the micropattern with more adhesive area.
Keywords: cell front-rear polarization, cell migration, dynamic micropatterning